Monolith, the colonial face of landscape photography. Issue 1 (2nd January 2022) - Devadoss, Christabel
Abstract: The goal of this paper is to highlight gendered, racial, and colonial politics of landscape photography by examining intersections of patriarchy, Orientalism/colonialism, and representation in its history and current practice. Landscape photography appears on or in screensaver backgrounds, TV commercials, cover art for apps or music, marketing campaigns, posters, textbooks, waiting rooms, corporate offices, hotel rooms, departmental promotional materials, study abroad brochures, among other materials in commercial, public, and private spaces. Despite its proliferation, the field's practice and roots are rarely addressed. In academia, scholars have separately examined both photographic and environmental discourse as tools of patriarchy and colonialism. As a former professional photographer-turned-academic and woman of South Asian descent, I draw from both my professional and academic perspectives to contribute to and bridge this dialogue. Through examination and analysis of historical and current representation, I demonstrate that landscape photography discourse perpetuates colonial practice and propagates gendered and racial stereotypes. More specifically, I highlight some of the ways that popular landscape photography in the West promotes white, Western colonialism and excludes narratives of women and people of color.